The first move : a negotiator's companion - Lempereur, Alain (Wiley, 2010)
Solidly and uniquely grounded in the best of European and American traditions and scholarship, including the authors' own research, this book provides deep insight into how to negotiate successfully in business and political settings alike. "There are two European negotiation scholars whose work is well known in the US and gloablly. Alain Lempereur is by discipline a lawyer. His training in negotiation was at Harvard Law School particularly influenced by Robert Mnookin. Lempereur writes for practitioners; Colson for academics. Lempereur is a prolific writer.